The role of adenosine signaling pathway in regulation of metabolic reserves - Okrouhlíková, Monika (Jihočeská univerzita, 2012)
This thesis presents a study of possible role of the extracellular adenosine signaling pathway in the regulation of metabolism of energetic reserves in Drosophila melanogaster. I focus on a study of metabolism of carbohydrate reserves and show a connection of adenosine signaling pathway to regulation of glucose homeostasis. Results of hemolymph and whole larval and pupal carbohydrates concentration measurements are shown together with concentration of other metabolites. They suggest that glucose homeostasis is impaired in the adgf-a mutant, which is accompanied by impaired metabolism of energetic reserves. The work is based on genetic screening for dominant suppressors of larval lethality caused by a loss of function mutation in the main larval adenosine deaminase, ADGF-A. Possible interactions of adenosine signaling pathway and regulation of immune response are disscussed.
The role of adenosine signaling pathway in regulation of metabolic reserves